2001
DOI: 10.1046/j.1468-1331.2001.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal P3 under different attentional states in mesial temporal lobe epilepsy

Abstract: The results suggest a modality dependence of the P3 component in patients with mTLE. The novelty processing of auditory stimuli is disturbed in patients with right sided mTLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Event-related potential (ERP) is an important method to evaluate the cognitive status of epilepsy patients (e.g., Sunaga et al, 1994;Soysal et al, 1999;Rodin et al, 1999;Tendon and Duban, 2000;Trinka et al, 2000;Sun et al, 2007). Differences in timing and scalp topography of particular ERP components allow inferences about the timing and spatial characteristics of brain activity involved in cognitive processing (Rugg and Coles, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Event-related potential (ERP) is an important method to evaluate the cognitive status of epilepsy patients (e.g., Sunaga et al, 1994;Soysal et al, 1999;Rodin et al, 1999;Tendon and Duban, 2000;Trinka et al, 2000;Sun et al, 2007). Differences in timing and scalp topography of particular ERP components allow inferences about the timing and spatial characteristics of brain activity involved in cognitive processing (Rugg and Coles, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The earliest identified member of this family, auditory ERP-P300, is used as an objective criterion for evaluating cognitive functions. Clinical studies showed delayed and smaller P300 in epileptics compared with controls; irregular waves can also be observed in those patients (Soysal et al, 1999;Rodin et al, 1999;Trinka et al, 2001). In the traditional auditory oddball paradigm, P300 is elicited by an event that is both infrequent and task relevant.…”
mentioning
confidence: 99%
“…This result suggests that the neural function of MTS patients does not contribute the neural synchrony necessary for the detection of subtle electrophysiological events. This finding was further supported by studies showing electrophysiologic abnormalities in event-related potentials (ERPs) recorded from patients with MTS 29 , which were not observed using a similar paradigm in the visual modality 30 .…”
Section: Discussionmentioning
confidence: 56%